An analysis of the effects of using Zolpidem and an innovative multimodal interdisciplinary team approach in prolonged disorders of consciousness (PDOC). (28th January 2019) - Delargy, Mark; O'Connor, Rebecca; McCann, Alison; Galligan, Irene; Cronin, Heather; Gray, Dee; O'Toole, Caoimhe
ABSTRACT: Zolpidem has been used with mixed effects in patients presenting with Prolonged Disorders of Consciousness (PDOC). This single case report describes an interdisciplinary team (IDT) protocol combined with Zolpidem 10 mg in a single case of a patient in PDOC. 'Emily', a 44-year-old lady was admitted to a rehabilitation unit in Ireland one year post onset of subarachnoid haemorrhage. Standardized assessments diagnosed her as being in a minimally conscious state (MCS). An IDT protocol was devised to stimulate and record responses to sensory and pharmacological stimuli. The protocol was applied pre and post administration of Zolpidem 10 mg. Across standardized measures of awareness, improved results post-Zolpidem were recorded. Spontaneous, appropriate verbalization was the most significant change observed 30 min after administration of Zolpidem 10 mg. This ceased after approximately 2 h with Emily reverting to a non-verbal state. The combined effect of Zolpidem and the IDT protocol applied over an eight-week period resulted in durable functional and communicative gains for Emily, inferring neuro-plasticity. This report highlights the impact of a combined approach of intensive IDT intervention in conjunction with Zolpidem. The use of Zolpidem with this patient population warrants further investigation.